The teaching effectiveness and learners' satisfaction in distance education of the undergraduate programme for in-service teachers - Chong, Ai Peng; Yusuf, Norihan; Guo, Lina; Aliche, Charles; Ozturk, Murat; Mohd Daud, Shaffe (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
This paper seeks to present the teaching effectiveness and satisfaction in the Distance Education of the Undergraduate Programme for Teachers (Program Pensiswazahan Guru or PPG in Malay language) in the Universiti Putra Malaysia (UPM) for the 2015 academic session. The study aimed to understand the effectiveness and learners’ satisfaction of this particular educational programme based on learners’ viewpoints. The teaching effectiveness constructs comprised five dimensions: students’ development, assessment, course materials, online component and face-to-face component of the program. Data were collected from a sample of 31 undergraduate students from Bachelor of Education (Primary Education). Results exhibits a moderate level of both the effectiveness and learners’ satisfaction towards the PPG program. Analysis Pearson correlation indicates the assessment and content have significant moderate positive relationship on learners’ satisfaction. Findings from this research have implications for instructional technology administrators, distance educational course designers, and instructors who are implementing learning activities in the PPG programme.